2020
DOI: 10.1038/s41598-020-58491-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined cadmium-zinc interactions alter manganese, lead, copper uptake by Melissa officinalis

Abstract: farmland soil typical for the polish rural environment was used in pot experiment to estimate the impact of cadmium and zinc on the manganese, lead and copper uptake by lemon balm (Melissa officinalis L). Bioavailable and total forms of investigated metals in soil and metal concentrations in plants were determined by atomic absorption spectrometry. the plant photosynthesis indicators were also examined. Intensification of photosynthesis upon the high zinc and cadmium soil supplementation was observed. This eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 52 publications
0
19
0
1
Order By: Relevance
“…Substantial additive Zn–Cd effect was also recognized for Melissa officinalis. The Zn uptake and accumulation in either roots or above-ground parts in this plant was inversely proportional to the cadmium concentration in soil 42 .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Substantial additive Zn–Cd effect was also recognized for Melissa officinalis. The Zn uptake and accumulation in either roots or above-ground parts in this plant was inversely proportional to the cadmium concentration in soil 42 .…”
Section: Introductionmentioning
confidence: 81%
“…Unfortunately, the detailed mechanism of this process has not been fully recognized as yet. Investigations of Adamczyk-Szabela et al 42 clearly indicate that nutrients affect zinc uptake but the reverse process i.e. the nutrients uptake upon zinc presence cannot be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Transfer coefficients and bioaccumulation factors were calculated as ratios of cerium contents in roots and shoots related to cerium concentration in Hoagland solution, respectively [21,129,130]. The translocation factor was defined as the ratio of particular element content in shoots to its content in roots [131][132][133].…”
Section: Transfer Coefficient Bioaccumulation Factor Translocation mentioning
confidence: 99%
“…The final accumulation of ENPs creates novel environmental stress factors for living organisms. Regrettably, the resulting pattern is far from the simplicity, with complex additive interactions being rarely appreciated [21,22]. Obviously, further investigations in the subject are needed [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium is a toxic element. Indeed, our recent study showed that its supplementation to soil reduced the growth of the lemon balm ( Melissa officinalis L. ) plant and decreased all relevant photosynthesis indicators [18]. Copper and cadmium associated interactions have been scarcely studied so far.…”
Section: Introductionmentioning
confidence: 99%